Call for Boycott of Pro-Israel Products in MUI Fatwa: An Analysis of Tafsīr Maqaṣidi - Annisa Fitrah; Asrizal Saiin; Anwar M. Radiamoda (Al-Qudwah, 2024)
This research analyzes the call to boycott Israeli products issued by the Indonesian Ulema Council (MUI) from the perspective of maqāṣidic exegesis (tafsīr maqaṣidi). The maqāṣidic approach in interpreting the Qur'an emphasizes the objectives of Sharia (maqāṣid al-sharī'ah), which include the preservation of religion (ḥifẓ al-Dīn), preservation of life (ḥifẓ al-Nafs), preservation of intellect (ḥifẓ al-'Aql), preservation of wealth (ḥifẓ al-Māl), and preservation of the state (ḥifẓ al-Daulah). The MUI's fatwa committee supports the boycott as a form of solidarity, aligning with the principles of justice and humanity in Islam, while also challenging the genocide committed by Israel against the Palestinian people. This paper is a type of library research, utilizing descriptive-analytical analysis. The findings of this research affirm that the boycott is viewed as an act of "amr ma'ruf nahi munkar," an effort to prevent wrongdoing and promote goodness. In the context of ḥifẓ al-Nafs, this boycott aims to protect human life and dignity from oppression. In the context of ḥifẓ al-'Aql, the boycott raises awareness among Muslims about global political and humanitarian issues. From the aspect of ḥifẓ al-Māl, the boycott encourages the ethical use of wealth and supports products not involved in oppression. Lastly, from the perspective of ḥifẓ al-Daulah, the boycott contributes to maintaining domestic stability and influencing foreign policy that supports peace. Moreover, the MUI fatwa on boycotting Israeli products is consistent with the maqāṣid al-sharī'ah, emphasizing the importance of such actions in achieving the welfare of the Muslim community and global society.Abstrak: Penelitian ini menganalisis seruan boikot produk Israel yang dikeluarkan oleh Majelis Ulama Indonesia (MUI) dari perspektif tafsīrmaqaṣidi. Pendekatan maqashidi dalam menafsirkan Al-Qur'ān menekankan pada tujuan syariah (maqashid syariah), yaitu ḥifẓ al-Dīn(pemeliharaan agama), ḥifẓ al-Nafs (memelihara jiwa/kehidupan), ḥifẓ al-'Aql (memelihara akal), ḥifẓ al-Mal (memelihara harta), dan ḥifẓal-Daulah (memelihara negara). Komisi fatwa MUI mendukung pemboikotan sebagai bentuk solidaritas dan sejalan dengan prinsip keadilan dan kemanusiaan dalam Islam sekaligus menantang genosida yang dilakukan oleh Israel terhadap rakyat Palestina. Tulisan ini termasuk penelitian kepustakaan (library research), dan menggunakan analisis deskriptif-analitik. Hasil penelitian ini menegaskan bahwa boikot ini dipandang sebagai tindakan amar makruf nahi mungkar, sebuah upaya untuk mencegah kemungkaran dan mempromosikan kebaikan. Dalam konteks ḥifẓ al-Nafs, pemboikotan ini bertujuan untuk melindungi nyawa dan martabat manusia dari penindasan. Dalam konteks ḥifẓ al-'Aql, boikot meningkatkan kesadaran di kalangan umat Islam tentang isu-isu politik dan kemanusiaan global. Dari aspek ḥifẓ al-Mal, boikot mendorong penggunaan harta secara etis dan mendukung produk-produk yang tidak terlibat dalam penindasan. Terakhir, dari sisi ḥifẓ al-Daulah, boikot berkontribusi dalam menjaga stabilitas dalam negeri dan mempengaruhi kebijakan luar negeri yang mendukung perdamaian. Di sisi lain, fatwa MUI tentang pemboikotan produk Israel selaras dengan maqaṣid al-syari’ah, yang menekankan pentingnya tindakan tersebut dalam mencapai kesejahteraan masyarakat muslim dan masyarakat global.